The Implementation of Early Initiation of Breastfeeding and The Sucking Reflex in Newborns - Ermiati E; Restuning Widiasih; Anita Setyawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Early initiation of breastfeeding (IMD) is a program recommended by the government in increasing the breastfeeding success, achieving exclusive breastfeeding and reducing the infant mortality rates. The IMD is a process of mothers initiates breastfeeding within one hour after delivery of their baby. During an hour, the baby looks for his mother's nipples without help. This would be useful to increase the ability of the baby's sucking reflex. The IMD is implemented in the delivery room as part of the APN procedure, however limited study in Indonesia assessed the IMD procedure. This study is aimed to assess the implementation of IMD and the sucking reflect of newborns in a hospital in Bandung city. This design of the study was the quantitative descriptive approach. The samples were 30 newborns. The samples were chosen using the accidental sampling technique. There were two types of instruments which are an observation sheet to check the procedure of IMD, and an instrument to assess babies’ sucking reflex including rooting, sucking, and swallowing reflexes. The study findings described in a frequency distribution. This study found that 100% of deliveries were carried out IMD inappropriately, and 86.7% of babies' sucking reflects were not achieved. The study concluded that the implementation of IMD was not maximal, and would be affected babies had not succeeded in breastfeeding. It is expected that the hospital would implement IMD as the standard of maternity services.Keywords: Early Breastfeeding Initiation, Reflect